Evaluating the Impact of Cooperative Services on Dairy Farm Performance in North Cianjur: An Importance-Performance Analysis Approach - Dahri Tanjung; Alla Asmara; Yeti Lis Purnamadewi; Anita Ristianingrum; Intani Dewi; Liisa Firhani Rahmasari (Postgraduate, University of Mataram, 2025)
The Foot-and-Mouth Disease (FMD) outbreak has worsened the performance of dairy farming and Milk Producers Cooperative (KPS). Therefore, this study aims to evaluate the effectiveness of cooperatives in supporting dairy farmers in North Cianjur, Indonesia. Using Importance-Performance Analysis (IPA), we assess the role of cooperative services in the performance of its dairy farming members. The results indicate that livestock health and reproduction services are highly prioritized, while education and training programs need improvement, along with a significant relationship between the performance of cooperative services and the businesses of its members. These findings emphasize cooperatives' importance in sustaining small-scale dairy farming performance and provide recommendations for service enhancement.